Socioemotional Development during Adolescence: Evidence from a Large Macro Shock - Ghazala Azmat; Katja Maria Kaufmann; Yasemin Özdemir (Institute of Labor Economics (IZA), 2023)
We exploit a large quasi-exogenous shock to study the development of socioemotional skills during adolescence and the consequences for long-term behavior and labor market outlook. Using novel, longitudinal, microdata on cohorts of East German adolescents before and after a large macro shock (the German Reunification), we causally estimate the impact on socioemotional skills, finding substantial negative effects in the short run. These effects are substantially larger among those affected by the shock in their early adolescence (13-14 years old), relative to older adolescents (16-17 years old). Changes in socioemotional skills have a lasting (negative) impact on them as adults, especially among those affected early in their adolescence, in terms of their expressions of externalizing behavior (e.g., physical fighting) and behavioral control problems (i.e., substance abuse), as well as internalizing behavior (i.e., mental health) and in their (labor-market) optimism and expectations. This study highlights the permanent effects of uncertainty on socioemotional skills during formative years.
Keywords: D91; I12; I31; J13; J16; J24; 330; socioemotional development; youths; behavior; health; education